2017
DOI: 10.1002/2017gl073500
|View full text |Cite
|
Sign up to set email alerts
|

Crustal structure across the eastern North American margin from ambient noise tomography

Abstract: Passive tectonic margins, like the eastern North American margin (ENAM), represent the meeting of oceanic and continental material where no active deformation is occurring. The recent ENAM Community Seismic Experiment provides an opportunity to examine the crustal structure across the ENAM owing to the simultaneous deployment of offshore and onshore seismic instrumentation. Using Rayleigh wave phase and group velocities derived from ambient noise data, we invert for shear velocity across the ENAM. We observe a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(39 citation statements)
references
References 45 publications
(59 reference statements)
5
34
0
Order By: Relevance
“…Seismic data gathered by USGS in Virginia (close to the seismic profile in this study) support this thin-skinned model (Pratt et al 1988). Previous studies also interpret the eastern North Figure: A-A′, a seismic reflection profile of Pratt et al (1988Pratt et al ( , 2015; B-B′, crustal model of Dreiling and Mooney (2015); C-C′, S-wave velocity model of Shen and Ritzwoller (2016); D-D′, P-wave velocity model of Hales et al (1968) and Lewis and Meyer (1977); E-E′, P-wave velocity model of Holbrook et al (1994); F-F′: S-wave velocity model of Lynner and Porritt (2017). Red box in the inset map outlines the study area American margin as a strongly volcanic margin, which are generally indicated by the presence of dipping reflectors within the transitional crust and crustal underplating of igneous materials (Klitgord et al 1988;Tréhu et al 1989;Holbrook et al 1994;White and McKenzie 1989).…”
Section: Geological Settingmentioning
confidence: 81%
See 3 more Smart Citations
“…Seismic data gathered by USGS in Virginia (close to the seismic profile in this study) support this thin-skinned model (Pratt et al 1988). Previous studies also interpret the eastern North Figure: A-A′, a seismic reflection profile of Pratt et al (1988Pratt et al ( , 2015; B-B′, crustal model of Dreiling and Mooney (2015); C-C′, S-wave velocity model of Shen and Ritzwoller (2016); D-D′, P-wave velocity model of Hales et al (1968) and Lewis and Meyer (1977); E-E′, P-wave velocity model of Holbrook et al (1994); F-F′: S-wave velocity model of Lynner and Porritt (2017). Red box in the inset map outlines the study area American margin as a strongly volcanic margin, which are generally indicated by the presence of dipping reflectors within the transitional crust and crustal underplating of igneous materials (Klitgord et al 1988;Tréhu et al 1989;Holbrook et al 1994;White and McKenzie 1989).…”
Section: Geological Settingmentioning
confidence: 81%
“…The middle and lower crust extend only as far east as the rifted zone, where they terminate. The offshore ocean-continent transition is 100 km wide, with normal oceanic crust beginning immediately to the east (Holbrook et al 1994;Lynner and Porritt 2017). Beneath the profiles in the SCS rift, there is no distinct oceancontinent transition as seen on the mid-Atlantic margin, and the extended crust is extended from continent to the ocean.…”
Section: Rifting Marginmentioning
confidence: 95%
See 2 more Smart Citations
“…We invert for V sh and V sv separately using identical starting models and inversion parameters. Our initial model is set to AK135 (Kennett et al, ) below 100 km and 4.5 km/s in the upper 100 km without an artificial jump at the Moho to avoid low velocity artifacts (e.g., Lynner & Porritt, ). We tested several starting models with a spatially varying velocity jump at the Moho and found that the different starting models resulted in only minor deviations.…”
Section: Methodsmentioning
confidence: 99%